2003
DOI: 10.1097/00055735-200312000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Therapies with potential toxicity of neuro-ophthalmic interest

Abstract: Appropriate management requires prompt recognition of these associations. Practitioners should be familiar with these neuro-ophthalmic manifestations because they may present in the course of daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…A clinical trial with lenercept for treatment of relapsingremitting MS showed an earlier onset and increased number of clinical exacerbations in those treated with lenercept versus placebo [4]. There have also been a number of case reports of infliximab-associated demyelinating disease, including several instances of new onset, unilateral retrobulbar optic neuritis supported by radiographic evidence [5][6][7]. Treatment with steroids was instituted in these latter cases with rapid resolution of the event.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial with lenercept for treatment of relapsingremitting MS showed an earlier onset and increased number of clinical exacerbations in those treated with lenercept versus placebo [4]. There have also been a number of case reports of infliximab-associated demyelinating disease, including several instances of new onset, unilateral retrobulbar optic neuritis supported by radiographic evidence [5][6][7]. Treatment with steroids was instituted in these latter cases with rapid resolution of the event.…”
Section: Discussionmentioning
confidence: 99%